Expected Practice as a Novel Antibiotic Stewardship Intervention. (3rd December 2018) - Yadav, Kabir; Masuda, Eriko; Minejima, Emi; Spellberg, Brad
Abstract: "Expected practice" is a recently described method to alter clinical behavior. We implemented an expected practice around short-course antibiotic therapy, which was associated with decreased antibiotic utilization for multiple bacterial infections. Thus, we describe this expected practice as a novel, simple, and inexpensive tool to enhance antibiotic stewardship.